Sudden unexpected death in epilepsy: a review of literature and own observations - Marienko, L. B.; Marienko, K. M. (Zaporozhye Medical Journal, 2019)
The purpose. To analyze the current state of scientific data related to sudden unexpected death in epilepsy (SUDEP) based on the study of recent investigations presented in the sources of scientific information about definition and classification of SUDEP, its risk factors, epidemiological data, pathophysiology, validity of proposed biomarkers, results of post-mortem examinations, measures of SUDEP prevention and also to present own observations of deaths with their classification. Numerous studies of the recent years have demonstrated the high medical and social significance of the problem of sudden unexpected death in epilepsy, the prevalence of which in patients with epilepsy is 20 times higher than in the general population. The proven association of such a death with a generalized tonic-clonic seizure (GTCS) indicates a real potential threat to life of patients with an unfavorable pharmacoresistant course of the disease. Possible, but not definitively evident, risk factors for SUDEP could be nighttime seizures during sleep, absence of witnesses who could help, prone position during sleep, male gender, age of epilepsy onset before 16 years and its duration more than 15 years, psychiatric comorbidity, simultaneous use of several anti-epileptic drugs (AEDs) or absence of any treatment, symptomatic etiology of epilepsy, use of lamotrigine in idiopathic epilepsy. The exact pathophysiology of SUDEP is unknown. The proposed clinical, genetic, electrophysiological, radiological SUDEP biomarkers for the purpose of identifying individuals with an increased risk of sudden death also do not have sufficient evidence base. Possible preventive SUDEP measures include monitoring of patients’ night sleep with the use of acoustic and biosensor devices, special smart-watches, usage of oxygen mask during or immediately after GTCS. There is a need to inform patients, especially those with unsatisfactory adherence to treatment, about the possibility of sudden death in order to improve their compliance. The main measure of prevention is the search for effective treatment with the best seizure control and minimal AEDs side effects. At present, only this way has an evidence base for reducing the risk of SUDEP. Own observations that meet the criteria for different types of SUDEP are presented.